The impact of adverse childhood experiences on health service use across the life course using a retrospective cohort study. (July 2017) - Bellis, Mark; Hughes, Karen; Hardcastle, Katie; Ashton, Kathryn; Ford, Kat; Quigg, Zara; Davies, Alisha
Objectives: The lifelong health impacts of adverse childhood experiences are increasingly being identified, including earlier and more frequent development of non-communicable disease. Our aim was to examine whether adverse childhood experiences are related to increased use of primary, emergency and in-patient care and at what ages such impact is apparent. Methods: Household surveys were undertaken in 2015 with 7414 adults resident in Wales and England using random probability stratified sampling (age range 18–69 years). Nine adverse childhood experiences (covering childhood abuse and household stressors) and three types of health care use in the last 12 months were assessed: number of general practice (GP) visits, emergency department (ED) attendances and nights spent in hospital. Results: Levels of use increased with increasing numbers of adverse childhood experiences experienced. Compared to those with no adverse childhood experiences, odds (±95% CIs) of frequent GP use (≥6 visits), any ED attendance or any overnight hospital stay were 2.34 (1.88–2.92), 2.32 (1.90–2.83) and 2.67 (2.06–3.47) in those with ≥ 4 adverse childhood experiences. Differences were independent of socio-economic measures of deprivation and other demographics. Higher health care use in those with ≥ 4 adverse childhood experiences (compared with no adverse childhood experiences) was evident at 18–29 years of age and continued through to 50–59 years. Demographically adjusted means for ED attendance rose from 12.2% of 18-29 year olds with no adverse childhood experiences to 28.8% of those with ≥ 4 adverse childhood experiences. At 60–69 years, only overnight hospital stay was significant (9.8% vs. 25.0%). Conclusions: Along with the acute impacts of adverse childhood experiences on child health, a life course perspective provides a compelling case for investing in safe and nurturing childhoods. Disproportionate health expenditure in later life might be reduced through childhood interventions to prevent adverse childhood experiences.